Social class, social mobility, and mental health - Vanzella-Yang, Adam; Veenstra, Gerry (My University, 2025)
This study investigated the relationship between intergenerational mobility and mental health in Canada, a country with mobility rates higher than those of the United States but lower than those of Nordic countries. This study used uncommonly accurate income data for respondents and their parents and deployed advanced statistical methods to distinguish the effects of mobility from those of social positions of origin and destination. The analysis focused on intergenerational mobility in income and in education, two key dimensions of social class. The Kessler (K-10) scale of psychological distress was used to assess mental health.
Keywords: Education, training & learning; Health; Income, pensions, spending & wealth; Population & demography; Society & community